Association Between Genetic Polymorphisms of WNT1 Inducible Signaling Pathway Protein 1 and Uterine Cervical Cancer. (November 2018) - Lin, Yu-Hsiang; Hsiao, Yi-Hsuan; Yang, Shun-Fa; Liu, Yu-Fan; Hsu, Chun-Fang; Wang, Po-Hui
To date, no study has investigated the involvement of the single-nucleotide polymorphisms (SNPs) of WNT1 inducible signaling pathway protein 1 (WISP1) in uterine cervical cancer. Therefore, we conducted this study to explore the clinical implications of WISP1 SNPs in cervical cancer. One hundred and fifteen patients with invasive cervical cancer, 95 patients with preinvasive lesions, and 316 normal controls were enrolled. The WISP1 SNPs rs62514004, rs2929973, rs2977530, and rs2977537 were selected, and their genotypic distributions were determined through real-time polymerase chain reaction. Our findings showed that genotypes AG/GG in WISP1 SNP rs2977530 reduced the risk of invasive cervical cancer with AA as a reference; however, these genotypes did not reduce the risk of preinvasive lesions. By contrast, genotype AA in WISP1 SNP rs2977537 elevated the risk of invasive cervical cancer with GG/GA as a reference, but it did not elevate the risk of preinvasive lesions. Moreover, an additional integrated in silico analysis indicated that WISP1 rs2977537 altered the WISP1 expression recorded in the Genotype-Tissue Expression database. In conclusion, genotypes AG/GG in WISP1 SNP rs2977530 reduce the susceptibility of Taiwanese women to invasive cervical cancer, whereas genotype AA in rs2977537 increases the said risk.